Wordplay “Loss” in Translation: - Retno Wulandari Setyaningsih; Zullian Rezza Kurniawan (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2021)
Wordplay can be described as the way of making or using words to create additional meaning for some purposes. Using a qualitative approach, this study discusses the wordplay translation in literary work especially in dystopian fiction using Delabastita’s translation techniques of wordplay. The data derived from a novel entitled The Handmaid’s Tale by Margaret Atwood as the source text and its subsequent translation in Bahasa Indonesia entitled The Handmaid’s Tale – Kisah Sang Handmaid as the target text. From 50 data retrieved, the result shows that the most frequently applied technique in wordplay translation is Wordplay to Non-Wordplay that appears 25 times or 50%. The result of this study illustrates that the translation of wordplay in this literary work tends not to preserve the author’s style of writing but one of the author’s intended meanings.